Team adaptive improvisation: Bridging two worlds of the unforeseen. - Abrantes, A.; Passos, A. M.; Cunha, M. P. (11th INGroup Annual Conference, 2016)
We argue that team improvisation can constitute a form of team adaptation and contribute to team effectiveness by retaining knowledge acquired during the improvisational process. We sustain our argument by bridging two organizational constructs that have been ignoring each other for the last twenty years – improvisation and adaptation.